Co-existence of PrP(D) types 1 and 2 in sporadic Creutzfeldt-Jakob disease of the VV subgroup: phenotypic and prion protein characteristics - Cali, Ignazio (Sci Rep, 2020)
We report a detailed study of a cohort of sporadic Creutzfeldt-Jakob disease (sCJD) VV1–2 type-mixed cases (valine homozygosity at codon 129 of the prion protein, PrP, gene harboring disease-related PrP, PrP(D), types 1 and 2). Overall, sCJDVV1–2 subjects showed mixed clinical and histopathological features, which often correlated with the relative amounts of the corresponding PrP(D) type. However, type-specific phenotypic characteristics were only detected when the amount of the corresponding PrP(D) type exceeded 20–25%. Overall, original features of types 1 (T1) and 2 (T2) in sCJDVV1 and -VV2, including rostrocaudal relative distribution and conformational indicators, were maintained in sCJDVV1–2 except for one of the two components of T1 identified by electrophoretic mobility as T1(21). The T1(21) conformational characteristics shifted in the presence of T2, inferring a conformational effect of PrP(D) T2 on T1(21). The prevalence of sCJDVV1–2 was 23% or 57% of all sCJDVV cases, depending on whether standard or highly sensitive type-detecting procedures were adopted. This study, together with previous data from sCJDMM1–2 (methionine homozygosity at PrP gene codon 129) establishes the type-mixed sCJD variants as an important component of sCJD, which cannot be identified with current non-tissue based diagnostic tests of prion disease.